Cartesian and Baconian Approach in Science and Engineering - Pušenjak, Rudolf (Anali PAZU, 2022)
The paper treats two different research approaches, founded by Descartes and Bacon, which have the most influental impact in the science and engineering over the past four centuries. The approach of Descartes is deductive and his scientific view is universal. The approach of Bacon rests on the experiment and puts into force the induction as the method of making the conclusions. In the paper is shown, that the fusion of both approaches, which are insufficient individually, is very successful. Both principles are shown in our own researches on stationary and nonstationary oscillations of beams and electromechanical systems. Unexpected phenomena in such systems, which cannot be predicted in the frame of the Cartesian, but by Baconian principles, are treated.
Keywords: Cartesian and Baconian principles; nonstationary resonances; hinged-clamped beam; electromechanical systems